Reduksi Stres Caregiver Pasien Gangguan Jiwa dengan Pelatihan Manajemen Stres - Dyah Wahyuningsih; Widyo Subagyo; Mukhadiono Mukhadiono (JURNAL KEPERAWATAN MERSI, 2020)
Background: Preliminary survey data in Kedondong village got patients with mental disorders with a considerable number of 23 people. Psychological conditions experienced by the family feel desperate with the condition of family members who suffer from mental disorders and do not go away, feel shy, resigned, let, some shut down. The process of treatment of mental patients will be more conducive if caregiver is able to manage the stress experienced in caring for mental patients. For that, stress management training is very important for caregiver. Research method: The purpose of this study was to determine the effect of stress management training on stress caregiver for mental patients. The research design is "Quasy experimental pre posttest without control group". The study population was all families of mental patients in the Sokaraja Community Health Center. The research subjects were taken with a total sampling technique, with 40 houses. The research subjects were given treatment in the form of stress management training. The effect of stress management training on stress caregiver mental patients is tested with paired t test. Result : The results of the study were that there were caregiver stress score before stress management training 39,63 and after stress management training 29,23. Training of caregiver stress management with cognitive preparation and relaxation techniques and hypnotherapy can significantly decrease caregiver stress score (p value 0,000). The advice was  given that caregiver groups should be formed as a means of brainstorming and filled with caregiver stress management training activities or other activities so as to reduce the burden of the family during caring for the patient